(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Anxiety in recreational marathoners is a common trait observed recently. These marathoners not only go through a lot of physical but as well as mental exertion due to which it burdens them and triggers more anxiety in them. Anxiety before the marathon creates an impact on the marathoner’s performance. Anxiety is a natural human state and a vital part of an individual’s life. Objective: the primary objective of this study was to find if there was any relation between the level of anxiety and the performance of the marathoner. The secondary objective was to quantify the extent of pre competition anxiety in recreational marathoners. Methodology: 40 recreational marathoners, both male, and female who consented to participate were included in this observational study. Their previous marathon timing and level of anxiety were checked before the marathon and they were asked to record their current marathon timings. Result: There was a positive correlation seen between the level of anxiety and performance of the marathoner. Females were found to have more significant somatic trait and concentration disruption whereas male marathoners were found to have more worry component significant. Conclusion: This study concluded that there was a significant correlation between the performance of the recreational marathoner and the level of anxiety was found.